“MATHAR BOOK” TECHNOLOGY-BASED MATHEMATICS LEARNING INNOVATION: UTILIZATION OF AUGMENTED REALITY BOOKS TO INCREASE LEARNING EFFECTIVENESS - Prihatini, Atik; Dewi, Utami; Khairunnisa, Muna; Pramuditya, Surya Amami; Aminah, Neneng (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
The challenge often faced in the mathematics learning process is creating an exciting learning experience that can increase the effectiveness of student learning. This research aims to design a learning media using Augmented Reality Book technology in an educational context, focusing on creating an exciting learning experience for high school students. The research method used is Research and Design, which combines research and development stages to create an innovation based on user needs. Data collection was obtained from testing using a questionnaire to determine the suitability of learning media. Questionnaires were given to material experts, media experts, and practitioners. The results of the media expert questionnaire obtained an average percentage of 83% in the feasible category, the results of the material expert questionnaire obtained a percentage of 86.36% in the appropriate category, and the results of the questionnaire given to practitioners received a percentage of 87.06% in the proper category. Based on the research results, it can be concluded that the MathAR Book learning media is suitable for use as a mathematics learning media, significantly contributes to education development with Augmented Reality technology, and provides practical guidance for educators in creating a motivating learning environment.